Tailoring diradicaloid properties of expanded isophlorinoids with systematic core-modification - Ambhore, Madan D.; Shukla, Pragati; Gonnade, Rajesh G.; Anand, Venkataramanarao G. (Chemical Communications, 2022)
Herein, we describe the synthesis, structural diversity and diradicaloid characteristics of 38 pi core-modified aromatic expanded isophlorins with eight heterocyclic rings. The diradicaloid character of expanded isophlorinoid macrocycles was engineered by systematic structural modification. Depending on the nature of the link between the heteroatoms, they adopt planar and non-planar conformations. This large structural variation with a significant difference in the extent of aromaticity is correlated with the magnitude of their respective diradical character.

Multifunctional luminogens with synergy of aggregation-induced delayed fluorescence, two-photon absorption and photocurrent generation - Chatterjee, Abhijit; Narayanan, Sundaravalli; Thorat, Sachin; Malik, Ajay J.; Ambhore, Madan D.; Narayanan, Aswini; Sihag, Anil Kumar; Babu, Sukumaran Santhosh; Lahiri, Mayurika; Hazra, Partha (Chemical Communications, 2025)
In this study, we investigated the aggregation-induced delayed fluorescence (AIDF) properties of three luminogens - TN, TA, and TP. Our comprehensive theoretical analysis reveals a significant reduction in the Delta EST in their aggregated or solid-state, activating TADF, on a similar to mu s time-scale. Additionally, these luminogens demonstrate two-photon excited anti-Stokes photoluminescence emission and improved photocurrent generation, attributed to their strong charge transfer characteristics and longer singlet exciton lifetimes.